Influence of motor capacity of the lower extremity and mobility performance on foot plantar pressures in community-dwelling older women - Min Liu; Ning Kang; Yalu Zhang; Erya Wen; Donghui Mei; Yizhe Hu; Gong Chen; Dongmin Wang (Heliyon, 2024)
Objectives: To investigate the associations of motor capacity of the lower extremity and mobility performance in daily physical activities with peak foot plantar pressures during walking among older women. Methods: Using the data collected among 58 community-dwelling older women (68.66 ± 3.85 years), Pearson correlation and multiple linear regression analyses were performed to analyze the associations of motor capacity of the lower extremity (the 30-s chair stand test, the timed one-leg stance with eyes closed, and the Fugl-Meyer assessment of lower extremity), mobility performance in daily physical activities (the average minutes of moderate to vigorous physical activity every day and the metabolic equivalents), and foot plantar pressures (peak force and peak pressure) with the age and body fat percentage as covariates. Results: (1) The motor capacity of the lower extremity has higher explanatory power for peak foot plantar pressures compared with the mobility performance in daily physical activities. (2) Higher body fat percentage was positively associated with peak force and pressure, while a lower score on the Fugl-Meyer assessment of lower extremity was negatively associated with both of them. (3) The metabolic equivalents were positively associated with the peak force, while the 30-s chair stand test was negatively associated with it. Conclusions: Mobility performance in daily physical activities can be significant predictors for peak foot plantar pressures among older women. The significant predictor variables include the Fugl-Meyer assessment of lower extremity, the 30-s chair stand test, and metabolic equivalents.